Variation in zinc, iron and quality parameters in wheat lines at different sowing locations - Jhinjer, Ramandeep Kaur; Mavi, Gurvinder Singh; Sood, Neerja; Malhotra, Akhil; Kaur, Harinderjeet; Kumar, Vineet; Bhagat, Indoo; Sohu, Virinder Singh (Vital Biotech, 2018)
Fifty lines of bread wheat representing 5th Harvest Plus Yield Trial were grown at three sites to identify genetically determined differences in micronutrient concentrations. Zn concentration showed positive and significant correlation with Fe concentration. Both Zinc (Zn) and Iron (Fe) concentrations correlated positively and significantly with grain protein, test weight and grain appearance score. Correlation of phenolic reaction score with Fe concentration was strong but with Zn concentration was week. Both Zn and Fe concentrations correlated negatively and significantly with days to heading, thousand grain weight, SDS (Sodium dodecyl sulphate) sedimentation value and grain yield. Both Ze and Fe concentrations showed negative direct effect on grain yield. Analysis of variance showed significant differences between genotypes, locations and interactions between genotypes and locations for grain Fe and Zn. 5th HPYT entry 409 had the highest mean Zn concentration (50.17 ppm), followed by 449(48.63 ppm), 412(48.21 ppm), 443(47.58 ppm) and 404(47.27 ppm). In case of Fe mean concentration, HPYT entry (449) had the highest value (53.81 ppm), followed by 409(51.71 ppm), 412(50.74 ppm), 436(49.25 ppm) and 443(49.25 ppm). Mean data from three locations showed one entry (417) yielded the more than the mean of the check (104%), while entry (410) yielded 98% of the check. Pooled data across locations showed an increment of 20.3% (50.17 ppm) over the check (41.71 ppm) for Zn. Eleven entries showed more than half of the target Zn (4 ppm) and 2 entries with more than full target Zn (8 ppm). The results from this study are useful for developing micronutrient biofortification strategies.